A heat-resistant polyamide composite material and a preparation method and application thereof

By adding carboxylated polyarylene ether nitrile and glass fiber to polyamide composites, a stable chemical structure is formed, which solves the problem of insufficient thermal stability and strength of nylon materials under high temperature conditions, and realizes polyamide composites with high strength and high thermal stability.

CN117777715BActive Publication Date: 2025-12-09TIANJIN KINGFA NEW MATERIAL +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311805702.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-12-09
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

Existing nylon materials lack sufficient heat resistance and strength retention in heavy industrial equipment and industrial construction, making it difficult to meet the requirements for long-term operation at high temperatures.

Method used

By adding carboxylated polyarylene ether nitrile and glass fiber to polyamide composites, the reaction of carboxyl groups with the amino groups at the ends of nylon molecular chains forms a stable chemical structure, which improves the thermal stability and intermolecular forces of the material and enhances the bonding force between nylon and glass fiber.

Benefits of technology

It significantly improves the thermal stability and mechanical properties of polyamide composites, with a strength retention rate of ≥73% and an initial decomposition temperature of ≥440℃, making it suitable for high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004630182120000061
    Figure BDA0004630182120000061
  • Figure BDA0004630182120000071
    Figure BDA0004630182120000071
  • Figure BDA0004630182120000081
    Figure BDA0004630182120000081
Patent Text Reader

Abstract

The application discloses a kind of heat-resistant polyamide composite material and preparation method and application thereof, belong to high polymer material technical field, the heat-resistant polyamide composite material described in the application includes the following weight parts of component: 48~102 parts nylon resin, 1.8~11 parts polyarylether nitrile, 45~78 parts glass fiber;The polyarylether nitrile is carboxylated polyarylether nitrile;The end amino content of the nylon resin is 80~90mmol / kg.The polyamide composite material described in the application is excellent in thermal stability, mechanical strength and strength retention rate, and is suitable for heavy industrial equipment field, industrial building field such as the field that material has high temperature resistance and high strength requirement.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer materials, in particular to a heat-resistant polyamide composite material and a preparation method and application thereof. BACKGROUND

[0002] Nylon is widely used as an engineering material in various fields. With the continuous improvement of technical level, the types of products are also increasing. However, with the development of modern high technology, the products with durability, chemical resistance and complex structure design are gradually increasing, which puts forward higher requirements on the comprehensive performance of the materials. Especially when nylon is applied to heavy industrial equipment field or industrial building field, the nylon material used needs to meet the characteristics of high strength and high heat resistance, and also needs to meet the working condition under continuous high temperature, that is, it has a certain strength retention rate.

[0003] At present, the heat resistance of nylon material is generally improved by improving the additives. For example, CN103436008A discloses a kind of super high glass fiber reinforced nylon material and its preparation method, which adds a specific interface modifier to enhance the specific strength, tensile property and wet state retention rate of bending property of the nylon material.

[0004] CN111995864A discloses a kind of polyamide composition and its preparation method, which adds polyetherimide and polyarylether nitrile and additives to the polyamide to improve the flame retardant property and heat resistance of the polyamide composition, but the heat distortion temperature is 90-105℃, which still needs to be improved.

[0005] In view of this, the present application is proposed. SUMMARY

[0006] The present application aims to overcome the shortcomings of the prior art and provide a kind of heat-resistant polyamide composite material and its preparation method and application, the heat stability, mechanical strength and strength retention rate of the polyamide composite material are excellent, and it is suitable for heavy industrial equipment field, industrial building field and other fields that require high temperature resistance and high strength of the material.

[0007] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is as follows:

[0008] A kind of heat-resistant polyamide composite material, comprising the following components by weight: 48-102 parts of nylon resin, 1.5-11 parts of polyarylether nitrile, 45-78 parts of glass fiber;

[0009] The polyarylether nitrile is carboxylated polyarylether nitrile.

[0010] The end amino content of the nylon resin is 80-90 mmol / kg.

[0011] The present application combines the above various raw materials in a specific ratio. On the one hand, in the polyamide system, the carboxylated polyarylether nitrile is added, and when melt blending, the carboxyl group of the polyarylether nitrile and the terminal amino group of the nylon molecular chain react to form a stable chemical structure, which can effectively improve the stability of the polyamide composite material. When the polyamide composite material is heated, it will not degrade due to the instability of the resin end. It can also improve the intermolecular force. On the other hand, the carboxylated polyarylether nitrile is combined with the hydroxyl group on the surface of the glass fiber, thereby effectively improving the bonding force between the nylon and the glass fiber, further improving the intermolecular force, and increasing the amount of glass fiber added, thereby effectively improving the mechanical properties and thermal stability of the polyamide composite material.

[0012] The inventors of the present application have found that in the specific system of the present application, the performance of the material is mainly affected by the content of the terminal amino group of the nylon resin. By controlling the content of the terminal amino group of the nylon resin to be 80-90 mmol / kg, the terminal amino group can fully react with the carboxyl group of the polyarylether nitrile to form a stable chemical structure, thereby improving the mechanical properties and thermal stability of the polyamide composite material. If the content of the terminal amino group is too low, it cannot provide enough terminal amino group, resulting in incomplete reaction of the carboxyl group of the polyarylether nitrile, and thus performance degradation. If the content of the terminal amino group is too high, the thermal stability of the nylon will be poor, and it will be prone to decomposition and deterioration. In use, deformation and cracking may occur. High content of terminal amino group will also reduce the fatigue life of the nylon, leading to rapid failure of the material. Therefore, the present application controls the terminal amino group of the nylon resin to be 80-90 mmol / kg.

[0013] The amount of the nylon resin is 45-100 parts, for example, it can be 45 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, 102 parts, or a range formed by any two of the above values.

[0014] Preferably, the amount of the nylon resin is 50-100 parts.

[0015] The amount of the polyarylether nitrile is 1.8-11 parts, for example, it can be 1.8 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, or a range formed by any two of the above values.

[0016] Preferably, the amount of the polyarylether nitrile is 2-10 parts.

[0017] The amount of the glass fiber is 45-78 parts, for example, it can be 45 parts, 50 parts, 60 parts, 70 parts, 75 parts, 78 parts, or a range formed by any two of the above values.

[0018] Preferably, the amount of the glass fiber is 50-75 parts.

[0019] The end amino group content of the nylon resin is 80-90 mmol / kg, for example, it can be 80 mmol / kg, 82 mmol / kg, 84 mmol / kg, 85 mmol / kg, 87 mmol / kg, 89 mmol / kg, 90 mmol / kg, or a range formed by any two of the above values.

[0020] Preferably, the carboxyl content of the carboxylated polyarylether nitrile is 10-25 wt%, for example, it can be 10 wt%, 12 wt%, 15 wt%, 18 wt%, 20 wt%, 22 wt%, 25 wt%, or a range formed by any two of the above values. By controlling the carboxyl content of the carboxylated polyarylether nitrile, the polyamide composite material with excellent mechanical properties and heat resistance can be obtained. If the carboxyl content is too low, the heat resistance and mechanical properties will decrease, and the end amino group of the nylon cannot be fully reacted, resulting in too many end amino groups of the nylon, which will also lead to a decrease in heat resistance and mechanical properties. If the carboxyl content is too high, the thermal stability will decrease due to the high content of the active carboxyl group, resulting in a decrease in the use value.

[0021] Preferably, the glass transition temperature of the carboxylated polyarylether nitrile is 140-230℃, for example, it can be 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, or a range formed by any two of the above values. In the present application, by selecting a polyarylether nitrile with a lower glass transition temperature, the thermal stability of the material is effectively improved.

[0022] Preferably, the glass transition temperature of the carboxylated polyarylether nitrile is 170-175℃. Especially, by using a carboxylated polyarylether nitrile with a glass transition temperature of 170-175℃, the thermal stability of the material can be further improved.

[0023] The inventors of the present application have found that in the specific polyamide system of the present application, the carboxylated polyarylether nitrile mainly affects the thermal stability, mechanical strength, and strength retention rate of the polyamide composite material through the carboxyl content and the glass transition temperature. By controlling the glass transition temperature of the carboxylated polyarylether nitrile to be 140-230℃ and the carboxyl content to be 10-25 wt%, the thermal stability, mechanical strength, and strength retention rate of the composite material are further improved.

[0024] It should be noted that the carboxylated polyarylether nitrile is obtained by treating the polyarylether nitrile with a conventional carboxylation reagent. In the present application, the specific carboxylation reagent and treatment method are not limited, as long as the carboxyl content of the polyarylether nitrile meets the corresponding requirements.

[0025] Exemplary carboxylating agents include, but are not limited to, phosphoric acid, sulfuric acid, formic acid, acetic acid, benzoic acid, oxalic acid, citric acid, malic acid, tartaric acid.

[0026] Exemplary methods of preparing carboxylated poly(arylene ether nitrile) include adding 100 parts of poly(arylene ether nitrile) to 500-2000 parts of a carboxylating agent, reacting, washing, and drying to obtain carboxylated poly(arylene ether nitrile).

[0027] The reaction is carried out at a temperature of 100-120°C, and the reaction time can be 0.1-10 h.

[0028] Preferably, the nylon resin has an end amino group content of 82-89 mmol / kg.

[0029] In the heat-resistant polyamide composite of the present application, the weight percentage of the nylon resin is not less than 40%.

[0030] In the heat-resistant polyamide composite of the present application, the weight percentage of the glass fiber is not less than 35%.

[0031] Preferably, the nylon resin includes at least one of nylon 46, nylon 66, nylon 610, nylon 612, nylon 613, nylon 1010, and nylon 1313.

[0032] Preferably, the nylon resin includes at least one of nylon 66, nylon 610, and nylon 1010.

[0033] Preferably, the nylon resin has a relative viscosity of 2.0-3.5 dl / g, for example, 2.0 dl / g, 2.2 dl / g, 2.5 dl / g, 2.8 dl / g, 3.0 dl / g, 3.2 dl / g, 3.5 dl / g, or a range defined by any two of these values.

[0034] Preferably, the nylon resin has a relative viscosity of 2.6-2.7 dl / g.

[0035] Preferably, the glass fiber is an alkali-free glass fiber.

[0036] Preferably, the glass fiber has a diameter of ≤12 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or a range defined by any two of these values.

[0037] Preferably, the glass fiber has a diameter of 9-12 μm.

[0038] Preferably, 0.1-10 parts of an auxiliary agent are further included, for example, 0.1 parts, 0.5 parts, 1 part, 2 parts, 4 parts, 5 parts, 6 parts, 8 parts, 10 parts, or a range defined by any two of these values.

[0039] Preferably, the adjuvant comprises at least one of a lubricant, a nucleating agent, an antioxidant, an antistatic agent.

[0040] The polyamide composite material described in the present application can comprise a lubricant, suitable lubricants include but are not limited to polyethylene wax, fatty acid ester, hyperbranched amide, and combinations thereof.

[0041] The polyamide composite material described in the present application can comprise a nucleating agent, suitable nucleating agents include but are not limited to sodium phenylphosphinate, silicon dioxide, talc powder, and combinations thereof.

[0042] The polyamide composite material described in the present application can comprise an antioxidant, suitable antioxidants include but are not limited to antioxidant 1098, antioxidant 1010, antioxidant 1076, antioxidant 168, and combinations thereof.

[0043] The polyamide composite material described in the present application can comprise an antistatic agent, suitable antistatic agents include but are not limited to zinc oxide, manganese dioxide, chromium trioxide, and combinations thereof.

[0044] The present application also provides a preparation method of a heat-resistant polyamide composite material, comprising the following steps: uniformly mixing the components except for glass fibers according to the ratio, feeding into a double screw extruder for melt mixing, feeding glass fibers, extruding and granulating to obtain the heat-resistant polyamide composite material.

[0045] Preferably, the length-diameter ratio of the screw of the double screw extruder is (40-48):1, for example, it can be 40:1, 42:1, 45:1, 48:1 or a range composed of any two of the above values.

[0046] Preferably, when melt mixing in the double screw extruder, the barrel temperature is 240-270℃, for example, it can be 240℃, 250℃, 260℃, 270℃ or a range composed of any two of the above values.

[0047] Preferably, when melt mixing in the double screw extruder, the screw rotation speed is 200-550rpm, for example, it can be 200rpm, 300rpm, 400rpm, 500rpm, 550rpm or a range composed of any two of the above values.

[0048] The present application also provides an application of the heat-resistant polyamide composite material in the field of heavy industrial equipment or industrial construction.

[0049] The polyamide composite material described in the present application has excellent thermal stability, mechanical strength and strength retention rate, and is suitable for the field of heavy industrial equipment, industrial construction and other fields which require high temperature resistance and high strength of materials.

[0050] The application has the beneficial effects that: the application can effectively improve the stability of the polyamide composite material by adding the carboxylated polyarylether nitrile in the polyamide system, reacting the carboxyl of the polyarylether nitrile and the end amino group of the nylon molecular chain to form a stable chemical structure when melt blending, and the material will not degrade due to the instability of the resin end when the polyamide composite material is heated, and the intermolecular force can be improved. On the other hand, the carboxylated polyarylether nitrile is combined with the hydroxyl on the surface of the glass fiber, thereby effectively improving the bonding force of the nylon and the glass fiber, further improving the intermolecular force, and increasing the amount of glass fiber added, thereby effectively improving the mechanical properties and thermal stability of the polyamide composite material. The strength retention rate of the polyamide composite material of the application is ≥73%, and the initial decomposition temperature is ≥440℃. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical scheme and advantages of the embodiments of the present application more clear, the technical scheme in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0052] In the present application, the technical features described in an open manner include both the closed technical scheme consisting of the listed features and the open technical scheme containing the listed features.

[0053] In the present application, if no special description is provided, the numerical range is regarded as continuous and includes the minimum value and the maximum value of the range and each value between the minimum value and the maximum value. Further, when the range refers to an integer, each integer between the minimum value and the maximum value of the range is included. In addition, when multiple ranges are provided to describe a feature or a property, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all sub-ranges subsumed therein.

[0054] The raw materials used in the examples and comparative examples are described as follows:

[0055] PA66-1: PA66, EP158NH, end amino group content 85 mmol / kg, relative viscosity 2.6, Hu Feng Group Co., Ltd.

[0056] PA66-2: PA66, MTR27, end amino group content 82 mmol / kg, relative viscosity 2.65, Cixi Jie Da

[0057] PA66-3: PA66, U4591, end amino group content of 88 mmol / kg, relative viscosity of 2.64, Invista.

[0058] PA66-4: PA66, EP127HL, end amino group content of 50 mmol / kg, relative viscosity of 2.67, Huafeng Group.

[0059] PA66-5: PA66, EP126NH, end amino group content of 110 mmol / kg, relative viscosity of 2.67, Huafeng Group.

[0060] PA610: FC1502, end amino group content of 88 mmol / kg, relative viscosity of 2.65, Guangyin New Material.

[0061] Glass fiber-1 : ECS10-3.0-T435N, Taishan Group, diameter of 10 pm.

[0062] Glass fiber-2: ECS13-4.5-560A, Giant Stone Group, diameter of 13 pm.

[0063] Auxiliary: antioxidant 1098, BASF.

[0064] Carboxylated polyarylether nitrile-1 : Tg (glass transition temperature) of 173 °C, carboxyl content of 20 wt%.

[0065] Carboxylated polyarylether nitrile-2: Tg (glass transition temperature) of 170 °C, carboxyl content of 25 wt%.

[0066] Carboxylated polyarylether nitrile-3: Tg (glass transition temperature) of 175 °C, carboxyl content of 10 wt%.

[0067] Carboxylated polyarylether nitrile-4: Tg (glass transition temperature) of 148 °C, carboxyl content of 20 wt%.

[0068] Carboxylated polyarylether nitrile-5: Tg (glass transition temperature) of 225 °C, carboxyl content of 20 wt%.

[0069] Carboxylated polyarylether nitrile-6: Tg (glass transition temperature) of 173 °C, carboxyl content of 6 wt%.

[0070] Carboxylated polyarylether nitrile-7: Tg (glass transition temperature) of 173 °C, carboxyl content of 33 wt%.

[0071] The preparation method of carboxylated polyarylether nitrile-1 to carboxylated polyarylether nitrile-7 is as follows (the selection of polyarylether nitrile in the preparation of carboxylated polyarylether nitrile, the glass transition temperature and the amount of carboxylation reagent are shown in Table 1) :

[0072] 100 parts by weight of polyarylether nitrile is placed in a reaction kettle, and a prepared carboxylation reagent (phosphoric acid and 10% dilute sulfuric acid in a volume ratio of 3:1) is added. The reaction kettle is heated to 110 DEG C, vacuumized to 0.06 Mpa, and reacted for 0.2 h. After filtration, washing with pure water, filtration and drying in a dehumidifying dryer at 130 DEG C for 0.6 h, a carboxylated polyarylether nitrile resin is obtained for standby use.

[0073] Table 1

[0074]

[0075]

[0076] The component raw materials used in the embodiments and comparative examples of the present application are commercially available raw materials unless otherwise specified, and the component raw materials used in each parallel experiment are the same.

[0077] The test standards of raw material parameters are as follows:

[0078] In the present application, the test method of the end amino group content of the nylon resin is as follows: the end amino group content of the sample is titrated by using a full-automatic potentiometric titrator. 0.5 g of the nylon resin sample to be measured is added into a mixed solution of phenol (45 mL) and anhydrous methanol (3 mL), heated to reflux, and observed until the sample is completely dissolved. Then, the solution is cooled to room temperature, and the end amino group content is titrated by using a calibrated hydrochloric acid standard solution.

[0079] In the present application, the test method of the relative viscosity of the nylon resin is as follows: the relative viscosity of the nylon resin with a concentration of 0.01 g / dL is measured in 98% concentrated sulfuric acid at 25±0.01 DEG C.

[0080] In the present application, the carboxyl content of the carboxylated polyarylether nitrile is tested by using ultraviolet absorption spectroscopy (detection wavelength 240 nm, and the carboxyl content is calculated according to Lambert-Beer law).

[0081] In the present application, the glass transition temperature of the carboxylated polyarylether nitrile is tested by using dynamic thermal mechanical properties, and the test standard is ASTM D6382-99 (2005).

[0082] In the present application, the test method of the diameter of the glass fiber is as follows: 100 glass fiber samples are placed under a microscope for observation, and the diameters of all the glass fibers in the samples are calculated to obtain the diameter of the glass fiber.

[0083] Examples and Comparative Examples:

[0084] The components and parts by weight of the heat-resistant polyamide composite materials of the examples and comparative examples are shown in Tables 2-4 (all in parts by weight).

[0085] The preparation method of the heat-resistant polyamide materials of the examples and comparative examples both includes the following steps:

[0086] According to the ratio, mix the components except for the glass fiber uniformly, put them into a double screw extruder for melt mixing, feed the glass fiber, extrude and granulate to obtain the heat-resistant polyamide composite material, wherein the length-diameter ratio of the screw of the double screw extruder is 44:1, and when melt mixing is carried out in the double screw extruder, the barrel temperature is 240-270℃, and the screw rotation speed is 200-550 rpm.

[0087] Table 2

[0088]

[0089] Table 3

[0090]

[0091]

[0092] Table 4

[0093]

[0094] Performance test

[0095] Strength retention rate test: the prepared material is injected and stretched in an injection molding machine at 275℃, using a 280T injection molding machine at a rated speed of 55% and a pressure of 50bar. The prepared sample is aged at 160℃ for 1000 hours, and then the tensile strength test is carried out, compared with the strength of the material before aging, to test the retention rate of the material strength, wherein the tensile strength is tested according to ISO527-2012-2 (1A sample, test speed is 10mm / min, temperature is 23±2℃, humidity is 50±6%).

[0096] Thermal stability test: the material sample is tested by TGA, from 30℃ to 450℃, the heating rate is 20℃ / min, nitrogen atmosphere, after 3min, switch to oxygen atmosphere, continue to heat to 650℃, record the initial temperature of 2% degradation of the material. The higher the initial temperature, the better the thermal stability of the material.

[0097] Table 5

[0098]

[0099]

[0100] As can be seen from Table 5, the polyamide composite material described in the application has excellent mechanical properties and thermal stability.

[0101] The strength retention rate of the polyamide composite material prepared in the application is ≥73%, and the initial decomposition temperature is ≥440℃.

[0102] As can be seen from Comparative Example 1 and Comparative Examples 1-3, the addition of the carboxylated polyarylene ether nitrile of the application significantly improves the mechanical properties and thermal stability of the composite material, and by controlling the amount of carboxylated polyarylene ether nitrile within the range defined in the application, the mechanical properties and thermal stability of the composite material are further improved. If the amount is too low, it cannot play a reinforcing role, and if the amount is too large, due to compatibility and residual unreacted groups, the performance will decrease.

[0103] As can be seen from Comparative Example 1 and Comparative Example 4, the carboxylated polyarylene ether nitrile used in the application has better effect than polyarylene ether nitrile, significantly improving the mechanical properties and thermal stability of the composite material.

[0104] As can be seen from Comparative Example 1 and Comparative Examples 5-6, by controlling the amount of nylon resin within the range of the application, the mechanical properties and thermal stability of the composite material are further improved. If the amount is too low, the compatibility and basic performance of the material will decrease significantly, further leading to performance degradation, and if the amount is too high, it will lead to too high content of terminal amino groups, resulting in poor thermal stability of nylon, easy decomposition and deterioration; deformation and cracking phenomenon easily occurs during use, and high content of terminal amino groups also reduces the fatigue life of nylon, leading to rapid failure of the material.

[0105] As can be seen from Comparative Example 1 and Comparative Example 7, by adding glass fibers, the mechanical properties and thermal stability of the composite material are significantly improved. As can be seen from the comprehensive comparison of Comparative Example 1 and Comparative Examples 1 and 7, the composite material described in the application has excellent mechanical properties and thermal stability, which is achieved under the joint action of nylon resin, carboxylated polyarylene ether nitrile and glass fibers. The surface groups of carboxylated polyarylene ether nitrile can be combined with both the molecular chain of polyamide resin and the glass fiber, and the comprehensive performance of the material is improved under the interaction of the three.

[0106] As can be seen from Comparative Example 1 and Comparative Examples 8-9, by controlling the content of terminal amino groups of nylon within the range of the application, the mechanical properties and thermal stability are significantly improved.

[0107] As can be seen from Comparative Example 1 and Example 8, the glass fiber with a diameter less than 12 μm is used in the application, further improving the mechanical properties and thermal stability.

[0108] As can be seen from the comparison between Comparative Example 1 and Examples 12-18, the mechanical properties and thermal stability are further improved by controlling the carboxyl content and glass transition temperature of the carboxylated polyarylene ether nitrile.

[0109] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present application and not to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the spirit and scope of the present application.

Claims

1. A polyamide composite, characterized in that, The composition comprises the following components by weight: 48-102 parts of a nylon resin, 1.8-11 parts of a polyarylether nitrile, 50-78 parts of glass fiber; The polyarylether nitrile is a carboxylated polyarylether nitrile; The end amino group content of the nylon resin is 80-90 mmol / kg; The carboxyl content of the carboxylated polyarylether nitrile is 10-25 wt%.

2. The polyamide composite according to claim 1, characterized in that, The glass transition temperature of the carboxylated polyarylether nitrile is 140-230 °C.

3. The polyamide composite of claim 1, wherein, The nylon resin comprises at least one of nylon 46, nylon 66, nylon 610, nylon 612, nylon 613, nylon 1010, and nylon 1313.

4. The polyamide composite of claim 1, wherein, The relative viscosity of the nylon resin is 2.0-3.5 dl / g, and the test method of the relative viscosity of the nylon resin is as follows: measuring the relative viscosity of the nylon resin with a concentration of 0.01 g / dL in 98% concentrated sulfuric acid at 25±0.01 °C.

5. The polyamide composite of claim 1, wherein, The glass fiber is an alkali-free glass fiber.

6. The polyamide composite of claim 1, wherein, The diameter of the glass fiber is ≤12 μm.

7. The polyamide composite of claim 1, wherein, 0.1-10 parts of an auxiliary agent are further included, and the auxiliary agent comprises at least one of a lubricant, a nucleating agent, an antioxidant, and an antistatic agent.

8. A process for the production of a polyamide composite according to any one of claims 1 to 7, characterized in that The method comprises the following steps: uniformly mixing the components except for the glass fiber according to the ratio, feeding them into a double-screw extruder for melt mixing, side feeding the glass fiber, extruding and granulating to obtain a polyamide composite material.

9. Application of the polyamide composite material according to any one of claims 1-7 in the field of heavy industrial equipment or industrial building.

Citation Information

Patent Citations

  • Ultrahigh-content glass fiber reinforced nylon material and preparation method thereof

    CN103436008A

  • Polyamide composition and preparation method thereof

    CN111995864A

  • Compatible polyamide-polyphenyl ether composition and preparation method thereof

    CN102627851A

  • Continuous-fiber-reinforced polyamide composite material prepreg tape and preparation method thereof

    CN103589138A